Stereoselective synthesis of 8,9-licarinediols - Nascimento, I. R.; Lopes, LMX; Davin, L. B.; Lewis, N. G. (Elsevier B.V., 2000)
The total synthesis of 8,9-licarinediols was selectively carried out from licarin A, previously obtained by oxidative coupling of (E)-isoeugenol. The corresponding enantiomerically pure (+)- and(-)-licarin A ester derivatives were subjected to Sharpless oxidation to yield the asymmetric C-8, C-9 dihydroxylation products, whose absolute configurations were established by means of the CD and NMR spectroscopic analyses of their Mosher ester derivatives. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: licarinediols; 2,3-dihydrobenzofuran lignans ligans; licarin A; synthesis; chiral separations; Mosher esters